The Peregrinations of Marco Antonio De Dominis, 1616–24 - Patterson, William B. (Studies in church history, 1978)
On 6 December 1616, Marco Antonio De Dominis, the Roman catholic archbishop of Spalato, on the Dalmatian coast, arrived in England. According to Arthur Wilson, he was ‘old and corpulent, unfit for Travel, being almost at his journies end by Nature’, yet he soon began to speak out vigorously against the faith and practices of Rome. Finding himself warmly welcomed by the archbishop of Canterbury and the king, he accepted several appointments in the church of England—including those of dean of Windsor and master of the Savoy—and became a prominent anti-Roman controversialist. Then, after five and a half years in England, De Dominis, like a wandering star in the Ptolemaic system, ‘went Retrograde, placing himself again in the Roman Calendar.’ What moved De Dominis to undertake so arduous a physical and spiritual journey as that which led him to England, and why, having found an honoured place among ideological allies, did he leave it to go to the very citadel of the ecclesiastical power he had attacked?